Expansion of the Strigolactone Profluorescent Probes Repertory: The Right Probe for the Right Application - de Saint Germain, Alexandre; Clavé, Guillaume; Schouveiler, Paul; Pillot, Jean-Paul; Singh, Abhay-Veer; Chevalier, Arnaud; Daignan Fornier, Suzanne; Guillory, Ambre; Bonhomme, Sandrine; Rameau, Catherine; Boyer, François-Didier (Frontiers in Plant Science, 2022)
Strigolactones (SLs) are intriguing phytohormones which regulate plant development and architecture but also interact with other organisms in the rhizosphere as root parasitic plants (Striga, Orobanche and Phelipanche) and arbuscular mycorrhizal fungi. Starting with a pioneering work in 2003 for the isolation and identification of the SL receptor in parasitic weeds, fluorescence labeling of analogs has proven a major strategy to gain knowledge in SL perception and signaling. Here, we present novel chemical tools for understanding SL perception based on the enzymatic properties of SL receptors. We designed different profluorescent SL probes (GC) and performed structure-activity relationship studies in both pea, Arabidopsis and Physcomitrium (formerly Physcomitrella) patens. Binding of GC probes to PsD14/RMS3, AtD14 and OsD14 proteins were tested. We demonstrated that coumarin-based profluorescent probes were highly bioactive and well-adapted to dissect the enzymatic properties of SL receptors in pea and a resorufin profluorescent probe in moss, contrary to the commercially available fluorescein profluorescent probe YoshimuLactone Green (YLG). These probes offer novel opportunities for the studies of SL in various plants.